2021
DOI: 10.3389/fonc.2021.659313
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Prognosis for Early Stage Cervical Cancer Patients (Stage IB1, IB2) Undergoing Surgical Treatment

Abstract: BackgroundFor individuals with cervical cancer, large tumor volume, lymph node metastasis, distant metastasis, and parauterine infiltration are usually associated with a poor prognosis. Individuals with stage 1B1 and 1B2 cervical cancer usually do not have these unfavorable prognostic factors. Once the disease progresses, the prognosis becomes extremely poor. Therefore, investigating the prognostic markers of these cervical cancer patients is necessary for treatment.MethodsThis retrospective study included 95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…This metabolic parameter is unavailable in conventional CECT scans and provides complementary information. Our SUV results are concordant with several other studies, which have also shown that this parameter in the primary tumor is an adverse prognostic factor and is associated with lymph node involvement and other features of biologically aggressive malignancy [19][20][21][22]. Given the higher spatial resolution of CECT or MRI and the metabolic information available with PET, the best imaging in clinically early-stage patients may be a combination of PET/CT and CECT or MRI.…”
Section: Discussionsupporting
confidence: 91%
“…This metabolic parameter is unavailable in conventional CECT scans and provides complementary information. Our SUV results are concordant with several other studies, which have also shown that this parameter in the primary tumor is an adverse prognostic factor and is associated with lymph node involvement and other features of biologically aggressive malignancy [19][20][21][22]. Given the higher spatial resolution of CECT or MRI and the metabolic information available with PET, the best imaging in clinically early-stage patients may be a combination of PET/CT and CECT or MRI.…”
Section: Discussionsupporting
confidence: 91%
“…However, the knowledge about the role of D-dimer in the prognosis of cervical cancer is relatively lacking. Chen et al and Kohei et al studies [14,22] have both shown that D-dimer is an independent prognostic factor for OS in cervical cancer patients. In elderly patients, D-dimer concentrations are higher than the upper limit for normal age, and continued use of standard D-dimer cut-off may compromise accuracy.…”
Section: Discussionmentioning
confidence: 95%
“…The “net” constructed by FIB in the extracellular matrix promotes cell adhesion and tumor invasion ( 30 ); in addition, FIB ultimately promotes angiogenesis and tumor growth by binding to growth factors such as vascular endothelial growth factor and fibroblast growth factor-2 ( 31 , 32 ). Previous studies have found that a high level of DD induces the progression of oral squamous cell carcinoma, cervical cancer, and glioma ( 13 , 19 , 33 ). In our study, the AUCs of FIB and DD for the diagnosis of meningioma progression were 0.615 and 0.593 in the training cohort, respectively, and their weighting coefficients in the HRM were 0.199 and 0.712, respectively; this also confirmed that high levels of FIB and DD were risk factors for the progression of AM.…”
Section: Discussionmentioning
confidence: 99%